2013
DOI: 10.1155/2013/316280
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Scoring of Antimicrobial and Biological Activities of Italian Vulnerary Plants against Major Oral Pathogenic Bacteria

Abstract: This study aims to evaluate the activity of Italian vulnerary plants against the most important oral pathogenic bacteria. This estimate was accomplished through a fivefold process: (a) a review of ethnobotanical and microbiological data concerning the Italian vulnerary plants; (b) the development of a scoring system to rank the plants; (c) the comparative assessment of microbiological properties; (d) the assessment of potential cytotoxic effects on keratinocyte-like cells and gingival fibroblasts in culture by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
0
26
2
Order By: Relevance
“…Our results, revealing weak effect of the herb extract on the cell proliferation of the non-cancerous cell line MCF10A compared to the cancer cells, are indicative for considerable selectivity in the antiproliferative effect. In regard to the cytotoxic properties towards non-cancerous cell lines a publication reported that ethanol and water extracts of the herb decreased cell viability of human gingival fi broblasts (HGF-1) and keratinocytes (HaCaT) in concentration of 5 mg/ ml, which is much higher than the doses applied in the present study [8].…”
Section: Disscussioncontrasting
confidence: 63%
“…Our results, revealing weak effect of the herb extract on the cell proliferation of the non-cancerous cell line MCF10A compared to the cancer cells, are indicative for considerable selectivity in the antiproliferative effect. In regard to the cytotoxic properties towards non-cancerous cell lines a publication reported that ethanol and water extracts of the herb decreased cell viability of human gingival fi broblasts (HGF-1) and keratinocytes (HaCaT) in concentration of 5 mg/ ml, which is much higher than the doses applied in the present study [8].…”
Section: Disscussioncontrasting
confidence: 63%
“…Because the current therapeutic strategies to prevent dental diseases are not entirely void of side effects, it should be necessary to develop new alternative approaches for clinical bacterial control. Recent research has demonstrated that plant extracts may be a suitable alternative treatment for caries [61][62][63][64][65]. Several plants products have been studied for their capability to contrast dental plaque formation, but a very limited number of these natural products has found therapeutic application, such as compounds rich in polyphenols [62].…”
Section: Future Researchmentioning
confidence: 99%
“…A large range of plant extracts have been shown to have antimicrobial effects and this can contribute to the development of new drugs, thus generating a significant improvement in management of various health disorders (20,32,33).…”
Section: Discussionmentioning
confidence: 99%